Current state of semi-anadromous and freshwater fisheries in Chukotka - Semen B. Baranov; Yulia A. Dyachkova (Известия ТИНРО, 2014)
Catch dynamics of semi-anadromous and freshwater fish in the internal waters of Chukotka is analyzed on the data of fisheries statistics for 2000-2013. Steady decline of catch volumes is observed since 2002. The data of anonymous polls on the problems of fisheries among local population in native villages are presented, and the data from the polls are compared with the official fisheries statistics that allows to estimate real values of catch.